2013
DOI: 10.1080/18756891.2013.809937
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Fuzzy Auto-Regressive Integrated Moving Average (FARIMAH) Model for Forecasting the Foreign Exchange Markets

Abstract: Improving forecasting especially time series forecasting accuracy is an important yet often difficult task facing forecasters. Fuzzy autoregressive integrated moving average (FARIMA) models are the fuzzy improved version of the autoregressive integrated moving average (ARIMA) models, proposed in order to overcome limitations of the traditional ARIMA models; especially data limitation, and yield more accurate results. However, the forecasted interval of the FARIMA models may be very wide in some specific Circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…The attacker's target is a random choice; as a result we can build a prediction model based on the time series and make use of the existing finite data to predict the future value. There are several basic time series models to choose from: the autoregressive (AR) model, the moving average (MA) model, and the autoregressive moving average (ARMA) model (36).…”
Section: Prediction Of the Next Targeted Clustermentioning
confidence: 99%
“…The attacker's target is a random choice; as a result we can build a prediction model based on the time series and make use of the existing finite data to predict the future value. There are several basic time series models to choose from: the autoregressive (AR) model, the moving average (MA) model, and the autoregressive moving average (ARMA) model (36).…”
Section: Prediction Of the Next Targeted Clustermentioning
confidence: 99%
“…The Forecasted interval of Fuzzy Auto-Regressive Integrated Moving Average models is extended in some specific data conditions [36]. According to the Ishibuchi and Tanaka opinion, forecasting interval can be too wide, when training data set includes the significant difference or outlying case [35].…”
Section: The Fuzzy Auto-regressive Integrated Moving Average (Farima)mentioning
confidence: 99%
“…Given the advantages of ANNs, it is not surprising that this methodology has attracted overwhelming attention in financial markets and especially exchange rate prediction. Numerous researchers have investigated ANNs for forecasting exchange rates and have shown that neural networks can be one of the very useful tools in foreign exchange markets forecasting (Khashei et al , 2013).…”
Section: Introductionmentioning
confidence: 99%